Tier 2 approaches for livestock: A collection of practices - Wilkes, Andreas (2018)
Expert workshop on Improving activity data for Tier 2 estimates of livestock emissions: Dealing with data gaps At the Hauge, July 17-18, 2018 Tier 2 estimates of livestock emissions: A collection of practices